Penerapan Prinsip Keadilan Dan Hak Asasi Manusia Dalam Penuntutan Oleh Jaksa - Nurwandri, Andri; Ilham, Muhammad; Rahmayani, Rahmayani; Harahap, Lila Mawaddah; Sitepu, Lily Amanda (CV. PUSDIKRA MITRA JAYA, 2024)
This research aims to determine the application of the principles of justice and human rights in prosecutions by prosecutors, where in carrying out their duties prosecutors must pay attention to human rights in the process of trying cases. The legal system of the Republic of Indonesia, as a democratic country based on law, has experienced significant developments over time. In carrying out its duties to maintain justice and public order, the judiciary has a central role in enforcing the law and prioritizing the principles of justice. In this context, prosecutors as an integral part of the justice system have an important responsibility in seeking justice based on the professional ethics of prosecutors.